Data Transmission Parameters of Reservoir Water PT. Meteor Perkasa Uses Long-Distance Communication - Natasya, Audrey Nanda; Marpaung, Jannus; Putra, Leonardus Sandy Ade (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The company engaged in the production of bottled drinking water (AMDK) is PT Meteor, the product produced is the "For3" brand product. The telecommunication system integration used is a telecommunication system The transmitter device is connected to the water parameterter sensor placed on the water storage source (Tandon), and the transmitter antenna is at a height of 8m. The receiving device is 80m, 180m, and 250m away from the transmitter with an antenna height of 1.5m above ground level. This study uses the RFM95W transceiver module to determine the test of sending sensor data from a water source using the LoRa gateway runs smoothly at the test points (distance) above. RSSI and SNR results show signal strength of -120dBm and -20dB. Although the distance is getting farther the value still looks positive, it can be said that the signal is good.